Hook or hatchet – Lover 's Lane, love scene epilogue - Ivan Kovačević (University of Belgrade, 2016)
Myth of a couple who escape death in a chance encounter with the psychopath with a hook instead of a hand, is one of the ten classic urban legends that have been brought to public attention by folklorists during the sixth and seventh decade of the twentieth century. Eminent Anglo-American folklorists dedicated entire papers, or significant portion in their works to this tale, as a contribution to the study of urban legends as a folk genre. In this essay, the legend of the hook is closely linked with the boyfriend's' death legend, its hermetic interpretation, and contextualization in the social reality of sexual relations at the time in which it occurs.